The slope of the tangent line is given by the derivative.

`y'(x)=3cos(3x)-2sin(2x)`

`y'(pi/6)=3cos(pi/2)-2sin(pi/3)`

`y'(pi/6)=0-sqrt(3)`

`y(pi/6)=sin(pi/2)+cos(pi/3)=3/2`

An equation of the tangent line at `x=pi/6` is `y=y'(pi/6)(x-pi/6)+y(pi/6)`

**Answer:** `y=-sqrt(3)(x-pi/6)+3/2`

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The slope of the tangent line is given by the derivative.

`y'(x)=3cos(3x)-2sin(2x)`

`y'(pi/6)=3cos(pi/2)-2sin(pi/3)`

`y'(pi/6)=0-sqrt(3)`

`y(pi/6)=sin(pi/2)+cos(pi/3)=3/2`

An equation of the tangent line at `x=pi/6` is `y=y'(pi/6)(x-pi/6)+y(pi/6)`

**Answer:** `y=-sqrt(3)(x-pi/6)+3/2`